Nelson Rodrigues, do fracasso ao ponto de vista do trágico - Paiva, Thalles Valente de (2021)
The objective of this research was to analyze the forms and the content of the tragedy and the tragic in the dramaturgical work of Nelson Rodrigues. Therefore, the central objective was to carry out an aesthetic and hermeneutic analysis. It is “obvious” that it is canonical that Nelson Rodrigues made tragedy and the tragic, and there are several defenses to these terms for the playwright's work. However, this dissertation defends that Nelson made tragedy in a contradictory and paradoxical way: your tragedy is a "failure", but that inherent "failure" is in the very structure of language and it is the foundation of the modernist tragedy. Therefore, my central argument, in a very Lacanian / Certeaunian way, is that: only is made tragedy and tragic in the modern era “failing”.